Atividade do óleo de Cymbopogon flexuosus livre e nanoestruturado frente a micobactérias de crescimento rápido - Rossi, Grazielle Guidolin (2018)
Rapidly Growing Mycobacteria (RGM) are emerging pathogens responsible for various human infections, although they are often considered only as contaminants or colonizers. The formation of biofilms by these microorganisms causes great concern for public health, due to its greater pathogenicity in humans and antimicrobial resistance. Microbial cells within the biofilm are protected by an autoproduced polymer matrix that delays the diffusion of antimicrobials, preventing the drug from penetrating the deeper layers and having its effective action. Thus, it is important to seek effective alternatives against the formation of biofilms. In this sense, the use of biological products as well as the use of nanostructures have been studied for the control of formation and development of biofilms. This work had as main objective to evaluate the action of the essential oil (EO) of Cymbopogon flexuosus free and in nanoemulsion on strains of RGM, in planktonic and sessile forms. EO was chemically characterized. The nanoemulsion obtained by the homogenization method under high stirring was characterized for its stability, surface charge and particle size. The assays of Minimum Inhibitory Concentration (MIC) and time-kill curve were determined against standard strains of RGM Mycobacterium abscessus (ATCC 19977), Mycobacterium fortuitum (ATCC 6841) and Mycobacterium massiliense (ATCC 48898). The ability of the oil and nanoemulsion to inhibit biofilm formation and to destroy it was evaluated by semi-quantitative macro technique. In the susceptibility test of the microorganisms in planktonic form, the nanoemulsion presented higher microbial activity, with MIC values lower than those presented by free EO. However, the free EO had bactericidal action, while the nanostructure had only bacteriostatic action. In the activity evaluation against RGM biofilms, both were efficient in the destruction of the biofilm already formed, while only the free oil inhibited the formation of mycobacterial biofilm. The results of this dissertation impact on the discovery of a new pharmacological formulation, capable of enhancing the effects of EO and impairing the formation of biofilms. In addition, this work stimulates the research in methodologies that aim to clarify the influence exerted by the EO and the nanoemulsion on the genetic and physiological factors associated with the biofilms formation.